Examine of the Facts of Women and Migration During the Urbanization in the Scale of South-eastern Anatolia Region (Gap), in Turkey - M. Oguz Sinemillioglu; Mine Baran (European Regional Science Association (ERSA), 2006)
Since the beginning of 1950's the migration of population from countryside to cities constitutes a subject as an important part of demographic changing on its own. Since the second half of 1970's, especially domestic migration from the small and medium size cities to big cities, by turning into family migration became dense in the three big metropolises in west. (Ýstanbul, Ankara, Ýzmir). In 1990's both the migration from east and Southeast Anatolia to other regions and the obligatory migration inside the region have been added to elements which effect movement of population. While this changing, which occurs in the dynamics of domestic migration during the time, does not exist in most of present researches, one of the other absence is social sex viewpoint. In the studies about migration, the lack of social sex viewpoint is not peculiar only to Turkey but also it seems limited in international literature. Present studies show there are important differences between women and men in the point of migration causes, participation to migration process, experiences during this process and effects of migration, attitudes and reactions of immigrants. In the core of these differences there are, collaboration inside the family between woman and man and parallel to this, social roles of woman and man, which described by customs and traditions. Women' life relating to migration is generally closely related to their situations in family as a wife, a mother or a young girl about to marry. The relations between them and both the places they left and they just came is formed in this base. Consequently, in a migration process, which includes a social and place changing, identity of sex has an important role as much as socio-economic class, culture, ethnic or national identity. G.A.P. Region which is in the Southeast of our developing country has a village-city appearance by the effects of both many side social, physiological, economic and urban destruction which created by terror and fight and generally the feudal structure in the region, extreme poverty, lack of top and underground structure and the political and economic choices which does not mind about neighborhood values. This work has aimed at examine to migration which is one of the most important social fact in the world we live in the context of woman and urbanization and to expose the appearance of women in extent of G.A.P. region in domestic immigration…
Keywords: 330